Penyuluhan mengenai Computer Vision Syndrome di Poliklinik Mata Rumah Sakit Citra Medika Sidoarjo - Ragil Anggoro; Silfiyani, Rahma; Susanto, Reinaldo Nathaniel; Kusumawardhany, Rini; Lestary, Atina Yustisia (Fakultas Kedokteran Universitas Sriwijaya, 2021)
The use of computers and digital electronic devices has increased during the pandemic. This can be a risk of developing Computer Vision Syndrome (CVS). Hang Tuah University has a program to bring prospective doctors closer to the community during medical professional education, namely through community service in the form of counseling about CVS. Community service is carried out at Citra Medika Hospital Sidoarjo, aiming to provide knowledge to the general public to prevent CVS, and reduce CVS cases. The material provided includes an introduction to CVS and its prevention efforts. Twenty respondents who were patients in the waiting room of the Eye Polyclinic followed the counseling well. Respondents were previously given a questionnaire regarding CVS. Most (17 people) had a low level of knowledge about CVS. Respondents were quite enthusiastic in the question-and-answer session and through observation, knowledge about CVS increased. Extension programs about CVS can increase public knowledge about CVS.